New records and confirmations of freshwater fish (Teleostei, Ostariophysi) from Uruguay after flood pulses from the Paraná and Uruguay rivers - Iván González-Bergonzoni; Ivana Silva; Cristhian Clavijo; Ricardo Juárez; Emilio Menvielle; Eugenio Lorenzo; Wiston Albieni; José Bessonart; Edgardo Bevilacqua; Facundo Cortondo; Anna Feris; Joaquín Pais; et al. (Check List)
Based on fish monitoring programs in the Uruguay River held during the 2023–2024 flood pulse, we report for the first time the presence of the following four species in the Uruguay river basin: Hemiodus orthonops Eigenmann & Kennedy, 1903; Cynopotamus kincaidi (Schultz, 1950); Brycon hilarii (Valenciennes, 1850); and Cnesterodon raddai Meyer & Etzel, 2001. Furthermore, three other species mentioned in literature but without formal records in scientific collections were confirmed for Uruguay: Schizodon borellii (Boulenger, 1900), Tetragonopterus argenteus Cuvier, 1816; and Hoplerythrinus unitaeniatus (Spix & Agassiz, 1829).